Simulation and Experimental Investigation Quenching Behavior of Medium Carbon Steel in Water Based Multi Wall Carbon Nanotube Nanofluids - Eissa, Ali Hussein; Hasan, Hala Salman (Al-Nahrain Journal for Engineering Sciences, 2020)
Experiments were conducted to study the effect of quenching medium carbon steel in water-based MWCNTs nanofluids at 0.05 % wt. concentration quenchant, a large cylindrical sample with 46 mm diameter and 40 mm length made from medium carbon steel used with three K-type thermocouples with a diameter of 1.5 mm inserted in three locations for sample (center of the sample, mid-point between center and surface and 1 mm from the surface). A time-temperature reading data system was used to read temperature history during cooling stage.The same experiments were simulated using ANSYS Workbench with Thermal Transient Version 19, the cooling curves at three locations for the cylindrical steel sample calculated during quenching in MWCNTs nanofluids. Quench factor analysis was used to predict the hardness results from the calculated and measured cooling curves, and these results compared with the hardness test results conducted in the significant sample from the center to the surface. The results show excellent compatibility when compared between the hardness results from cooling curves, and it also shows a good agreement with the results of the hardness test, especially at the sample surface.